High Density Surface Electromyography Activity of the Lumbar Erector Spinae Muscles and Comfort/Discomfort Assessment in Piano Players: Comparison of Two Chairs - Aranceta-Garza, Alejandra; Russo, Alessandro; D’Emanuele, Samuel; Serafino, Francesca; Merletti, Roberto (Frontiers in Physiology, 2021)
Introduction: At a professional level, pianists have a high prevalence of playing-related musculoskeletal disorders. This exploratory crossover study was carried out to assess and compare quantitatively (using HDsEMG), and qualitatively (using musculoskeletal questionnaires) the activity of the lumbar erector spinae muscle (ESM) and the comfort/discomfort in 16 pianists sitting on a standard piano stool (SS) and on an alternative chair (A-chair) with lumbar support and a trunk-thigh angle between 105° and 135°. Materials and methods: The subjects played for 55 min and HDsEMG was recorded for 20 s every 5 min. For the quantitative assessment of the muscle activity, the spatial mean of the root mean square (RMSROA) and the centroid of the region of activity (ROA) of the ESM were compared between the two chairs. For the qualitative assessment, musculoskeletal questionnaire-based scales were used: General Comfort Rating (GCR); Helander and Zhang’s comfort (HZc) & discomfort (HZd); and Body Part Discomfort (BPD). Results: When using the A-chair, 14 out of 16 pianists (87.5 %) showed a significantly lower RMSROA on the Left and Right side (p<0.05). The mixed effects model revealed that both chairs (F=28.21, p<0.001) and sides (F=204.01, p<0.001) contributed to the mean RMSROA variation by subject (Z=2.64, p=0.004). GCR comfort indicated that participants found the A-Chair to be “quite comfortable”, and the SS to be “uncomfortable”. GCR discomfort indicated that the SS caused more numbness than the A-Chair (p=0.05) and indicated the A-Chair to cause more feeling of cramps (p=0.034). No difference was found on HZc (p=0.091) or HZd (p=0.31) between chairs. Female participants (n=9) reported greater comfort when using the A-Chair than the SS (F=7.09, p=0.01) with respect to males. No differences between chairs were indicated by the BPD assessment. Conclusion: It is concluded that using a chair with lumbar support such as the A-chair, will provide greater comfort, less exertion of the ESM and less discomfort than the standard piano stool.